Creative Thinking in Constructing a Theatrical Presentation System: Educational Theater Performances as a Model - Reda Abdabuldhar Abd; Duaa Basem Ibrahim Ibrahim; Mohammed Ghani Jabbar Jabbar (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Educational theatre represents an interactive pedagogical approach that integrates artistic and educational dimensions through live performance and audience engagement. Specific Background: The construction of theatrical performance systems relies on the integration of directing, acting, scenography, and text, requiring structured yet flexible artistic coordination. Knowledge Gap: Despite its potential, many educational theatre practices remain constrained by traditional presentation patterns, limiting the application of creative thinking across performance elements. Aims: This study aims to reveal the concept of creative thinking and examine its role in constructing the theatrical performance system within educational theatre. Results: The findings indicate that performances based on psychological conflict, abstract scenography, and internal acting techniques stimulate reflective thinking, expand imagination, and promote intellectual interaction among audiences. Additionally, the integration of directing, acting, and scenography supports the delivery of educational values through indirect and non-preaching methods. Novelty: The study highlights creative thinking as a systemic and integrative process that reconfigures theatrical elements into a cohesive educational-artistic structure. Implications: These results suggest that educational theatre, when grounded in creative thinking, functions not merely as a presentation medium but as an intellectual tool that fosters critical awareness, imagination, and value-based learning. Highlights:• Psychological Conflict–Based Scripts Encourage Deeper Reflective Engagement in Audiences.• Abstract Staging Expands Interpretive Imagination Within Theatrical Experiences.• Integrated Performance Elements Support Value Transmission Through Indirect Expression. Keywords: Creative Thinking, Educational Theatre, Theatrical Performance System, Scenography, Acting Performance.